Selection of fertilization method and fertilizer application rate on corn yield - Bakhtiari, Mohammad Reza; Ghahraei, Omid; Ahmad, Desa; Yazdanpanah, Ali Reza; Jafari, Ali Mohammad (International Commission of Agricultural and Biosystems Engineering, 2014)
A field experiment was carried out on the silty clay soil of Lack-Lack agricultural research field during two years to select the most suitable fertilization method (fertilizer broadcasting, fertilizer pouring in the furrow, fertilizer banding placement in one side and both sides of seedling) and application rate (30, 60 and 90 kg of net nitrogen from source of urea fertilizer/ha) on corn yield and yield components in Hamedan province in Iran. Corn yield components evaluated were plant height, corn height, percentage of corncob, thousand-kernel mass and net yield. A factorial experiment with 12 treatments (four methods x three levels) was replicated three times in 36 test plots. By analysis of variance and comparison of treatment means using DMRT (Duncan's new Multiple Range Test), application methods had no significant effect on plant height, corn height and percentage of corncob, but net yield and thousand-kernel mass were highly influenced. In addition, effect of fertilizer application rate on plant height, corn height, and percentage of corncob was not significant but was highly significant on net yield and thousand-kernel mass. Interactional effects of method x level on plant height, corn height, percentage of corncob and thousand-kernel mass were not significant but their effects on net yield were very significant. In this study, fertilizer banding on one side of seedling with 60 kg of nitrogen/ha applied 10 cm from the seedling at 5 cm soil depth was selected as the most suitable treatment.